SYSTEMATIC LITERATURE REVIEW: KEPERILAKUAN DALAM PENGANGGARAN PEMERINTAHAN DAERAH [SYSTEMATIC LITERATURE REVIEW: BEHAVIOR IN LOCAL GOVERNMENT BUDGETING] - Wahyumi Ekawanti; Rinny Meidiyustiani; Shinta Utama Wati; Yulia Ardati (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to identify and understand behavior in local government budgeting practices. The study was conducted using a systematic literature review (SLR) method to identify and assess literature related to behavioral practices in local government budgeting. SLR was chosen because this method allows researchers to comprehensively review findings from previous studies, identify research gaps, and develop a robust conceptual framework based on available evidence. The findings of this study are that the behavior of budget actors in the budgeting process in Regional Government can be influenced by several theories, namely Agency Theory, Goal Theory, and Attribution Theory.